2015
DOI: 10.1542/peds.2015-2001
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Nonhemolytic Neonatal Hyperbilirubinemia

Abstract: BACKGROUND: Before hospital discharge, newborn infants should be assessed for the risk of excessive hyperbilirubinemia. We determined maternal and obstetric risk factors for hyperbilirubinemia in infants born at term (gestational age $37 weeks) to form an individualized risk assessment tool for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
30
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 39 publications
9
30
1
1
Order By: Relevance
“…Nevertheless, one of the authors (SJ) reported that one Swedish neonatology unit only recorded ICD codes for jaundice if the cases required phototherapy or exchange transfusion, as instructed in the national guidelines (9). Furthermore, the rates of jaundice reported for our 1987-2002 cohort were very similar to those recorded by Swedish cohort mentioned above, which covered 1999-2012 (13). Our rates of haemolytic jaundice were 0.59% and 0.49%, and the rates of nonhaemolytic jaundice in term infants were 2.2% and 1.9%, respectively.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Nevertheless, one of the authors (SJ) reported that one Swedish neonatology unit only recorded ICD codes for jaundice if the cases required phototherapy or exchange transfusion, as instructed in the national guidelines (9). Furthermore, the rates of jaundice reported for our 1987-2002 cohort were very similar to those recorded by Swedish cohort mentioned above, which covered 1999-2012 (13). Our rates of haemolytic jaundice were 0.59% and 0.49%, and the rates of nonhaemolytic jaundice in term infants were 2.2% and 1.9%, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…First, the importance of pregnancy risk factors such as older maternal age and higher maternal BMI for nonhaemolytic jaundice provide a plausible link between multiple disparate causes of nonhaemolytic jaundice. To our knowledge, the association with maternal obesity has only been previously reported in another publication based on a Swedish cohort (13). Mothers with higher BMI are more likely to have infants with complications such as birth trauma, bacterial sepsis and preterm birth, conditions that are linked with jaundice (16,17).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Maternal age and cesarean delivery are risk factors associated with hyperbilirubinemia (32, 33), as well as fertility treatment conceptions which may in part explain our finding.…”
Section: Discussionmentioning
confidence: 58%